Penicillamine-Induced Signs of Wilson Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A 9-year-old boy with asymptomatic Wilson disease who developed neurologic symptoms after treatment with penicillamine is reported from the Department of Pediatrics, Universita Federico II, Naples, Italy.